The influence of knowledge and financial literacy on the interest in saving for bank syari'ah students - Natania, Nadia; Muhlisoh, Muhlisoh; Wulandari, Wulandari; Haryadi, Didit (Institute of Computer Science (IOCS), 2024)
A country's high level of finance will encourage the development of its economy. Internal and external factors cause high and low financial management behavior. This study aims to develop a model that examines the three variables that the author has analyzed to determine the factors that can increase student interest in saving. This study used the associative descriptive quantitative method with a population of 89 respondents drawn into samples using non-probability sampling using saturated sampling / total sampling methods. Data analysis techniques using linear regression with the help of SPSS software version 26. The first hypothesis of knowledge significantly affects students' interest in saving, the second hypothesis of financial literacy variables has a significant impact on students' interest in saving, and the third hypothesis of knowledge and financial literacy together can affect students' interest in saving. This research is expected to make theoretical contributions to the literature in this context, including in the context of financial and banking management.